Estimating the risk of mortality attributable to recent late HIV diagnosis following admission to the intensive care unit: A single‐centre observational cohort study. Issue 11 (20th November 2022) - Bakewell, Nicholas; Kanitkar, Tanmay; Dissanayake, Oshani; Symonds, Maggie; Rimmer, Stephanie; Adlakha, Amit; Lipman, Marc C.; Bhagani, Sanjay; Agarwal, Banwari; Miller, Robert F.; Sabin, Caroline A.
Abstract: Objectives: Despite improvements in survival of people with HIV admitted to the intensive care unit (ICU), late diagnosis continues to contribute to in‐ICU mortality. We quantify the population attributable fraction (PAF) of in‐ICU mortality for recent late diagnosis among people with HIV admitted to a London ICU. Methods: Index ICU admissions among people with HIV were considered from 2000 to 2019. Recent late diagnosis was a CD4 T‐cell count < 350 cells/μL and/or AIDS‐defining illness at/within 6 months prior to ICU admission. Univariate comparisons were conducted using Wilcoxon rank‐sum/Cochran–Armitage/χ 2 /Fisher's exact tests. We used Poisson regression (robust standard errors) to estimate unadjusted/adjusted (age, sex, calendar year of ICU admission) risk ratios (RRs) and regression standardization to estimate the PAF. Results: In all, 207 index admissions were included [median (interquartile range) age: 46 (38–53) years; 72% male]; 58 (28%) had a recent late diagnosis, all of whom had a CD4 count < 350 cells/μL, and 95% had advanced HIV (CD4 count < 200 cells/μL and/or AIDS at admission) as compared with 57% of those who did not have a recent late diagnosis ( p  < 0.001). In‐ICU mortality was 27% (55/207); 38% versus 22% in those who did and did not have a recent late diagnosis, respectively ( p  = 0.02). Recent late diagnosis was independently associated with increased in‐ICU mortality risk (adjusted RR = 1.75) (95% confidence interval: 1.05–2.91), with 17.08% (16.04–18.12%) of deaths being attributable to this. Conclusions: There is a need for improved public health efforts focused on HIV testing and reporting of late diagnosis to better understand potentially missed opportunities for earlier HIV diagnosis in healthcare services.